PERANAN SEKTOR PERTANIAN TERHADAP KESEMPATAN KERJA DI KABUPATEN BARITO SELATAN - Frilia Christin; Betrixia Barbara; Evi Feronika (Program Studi Agribisnis Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Palangka Raya, 2018)
The purpose of this study is to know the role of agricultural sector in the absorption of the Labor In South Barito Regency. The data used in this study is secondary data. To answer this purpose, used labor number multiplier, shift share, pure forecast. The result of this Study indicates that the number of labor of agricultural sector in South Barito Regency is 1.6, which means that every increase of 1 labor of agriculture sector, it will open the job opportunity of other economic sector in South Barito Regency as much as 1 to 2 labors.